Apply the law, and do what you want? The concept of judicial independence and the prospective of a deontological model of judicial virtues - Rocławska, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
This article explores judicial independence in light of a deontological model of virtues. It analyses judicial decisions and attitudes in the process of application of law, arguing that their aspirations to pursue judicial virtues are a secondary requirement against an overriding demand for abiding by law. The thesis is that judicial independence is a kind of a system presupposition that judges have some qualities which help them not only to fulfil their duties, but also to rise to ethical challenges during adjudication. The author recalls two theories of judicial reasoning in hard cases and tries to answer the question which of the theoretical models – by H. L. A. Hart or R. Dworkin – proposes a better characteristic of the judicial practice in the Polish justice system.